2000
DOI: 10.1023/a:1006356502820
|View full text |Cite
|
Sign up to set email alerts
|

Shorter CAG repeat length in the androgen receptor gene is associated with more aggressive forms of breast cancer

Abstract: The androgen receptor (AR) is a transcription factor mediating the action of androgens. The AR gene is localized on chromosome X and it contains a series of CAG trinucleotide repeats. The length of the CAG repeats varies among individuals and this polymorphism is believed to be related to AR transcriptional activity. Studies have shown that fewer CAG repeats are associated with an increased risk as well as more aggressive forms of prostate cancer. Although AR is expressed in breast cancer and the impact of and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 20 publications
3
65
0
Order By: Relevance
“…24 Given the endocrine dependency of breast cancer and the effect that androgenic pathway has on breast tissue proliferation, 22,25 it is plausible that an increased androgen transactivation may promote uncontrolled breast epithelial tissue proliferation. As a further support for the putative role that the short CAG repeat plays in determining breast cancer phenotype, Yu et al 26 suggested an association between shorter CAG repeat length and tumour grade and survival. Several studies reported of an association between the shorter AR (CAG)n repeat and the risk for prostate cancer.…”
Section: Discussionmentioning
confidence: 97%
“…24 Given the endocrine dependency of breast cancer and the effect that androgenic pathway has on breast tissue proliferation, 22,25 it is plausible that an increased androgen transactivation may promote uncontrolled breast epithelial tissue proliferation. As a further support for the putative role that the short CAG repeat plays in determining breast cancer phenotype, Yu et al 26 suggested an association between shorter CAG repeat length and tumour grade and survival. Several studies reported of an association between the shorter AR (CAG)n repeat and the risk for prostate cancer.…”
Section: Discussionmentioning
confidence: 97%
“…By contrast, some studies have not confirmed this relationship (e.g. [56,57]), and Yu et al [58] found a negative correlation between CAG repeat length and tumor aggressiveness in breast cancer. There is also evidence that CAG repeats evolve through selection in the somatic evolution of colon cancer [59], which indicates that shorter repeat length, may be associated with other forms of cancer as well.…”
Section: Introductionmentioning
confidence: 92%
“…In breast cancer, shorter CAG tracts have been associated with a higher grade and with lymph node involvement. 5,36 In ovarian cancer no association was found between CAG fragment length and age at diagnosis, grade or stage. 12 Finally, the data related to prostate cancer is conflictive, although different reports have suggested that a shorter CAG repeat is predictive of a higher grade, lymph node-positive disease and an advanced stage.…”
Section: Discussionmentioning
confidence: 99%
“…The data published about the prognostic value of both repeats in other steroid-hormone related tumors differ from our findings in EC. Short CAG repeats have been found to be predictive of a worse clinical outcome in breast, 5 ovarian, 12 and prostate cancers. 9 Conversely, the short GGN alleles have been associated with a good prognosis in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation